1996
DOI: 10.1074/jbc.271.11.6129
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Inhibits PC Cl3 Thyroid Cell Proliferation through the Modulation of Phosphotyrosine Phosphatase Activity

Abstract: In this study, we report the effects of somatostatin on the proliferation of PC C13 thyroid cell line and the intracellular mechanisms involved. We also evaluated the possible alterations, induced by E1A oncogene transformation on the intracellular pathways mediating somatostatin inhibition of cell proliferation. We showed that somatostatin was able to powerfully inhibit insulin- and insulin + TSH-dependent cell proliferation by inducing a block in the G1/S progression in the cell cycle. These cytostatic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
38
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 31 publications
9
38
0
1
Order By: Relevance
“…We and others have demonstrated that somatostatin and analogues induce the stimulation of a membrane PTPase, which may be involved in the inhibitory effect of these peptides on cell proliferation (9,11,12,38). More recently, we have established the role of the somatostatin receptor sst2 in mediating the stimulatory effect of somatostatin on PTPase activity and its negative effect on cell growth (13,14).…”
Section: Discussionmentioning
confidence: 96%
“…We and others have demonstrated that somatostatin and analogues induce the stimulation of a membrane PTPase, which may be involved in the inhibitory effect of these peptides on cell proliferation (9,11,12,38). More recently, we have established the role of the somatostatin receptor sst2 in mediating the stimulatory effect of somatostatin on PTPase activity and its negative effect on cell growth (13,14).…”
Section: Discussionmentioning
confidence: 96%
“…TSH activates proliferation through the adenylyl cyclase/cAMP cascade in rat thyroid cell lines (2)(3)(4)(5)(6). In addition, TSH, via cAMP, regulates mRNA expression of HMG-CoA reductase and an active cholesterol biosynthetic pathway is required for DNA replication in FRTL-5 cells (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously this cell line was derived from the thyroid of 3-to 4-week-old rats (2), whereas the other cell line investigated in the current study, PC Cl3, was derived from 18-month-old rat thyroid (3). While numerous reports show that in FRTL-5, and to a lesser extent in PC Cl3 rat thyroid cells, proliferation is regulated mainly by insulin or insulinlike growth factor (IGF) and thyrotropin (TSH) (2)(3)(4)(5)(6) the regulatory mechanisms of cell mass doubling are still unclear. Recently our laboratory has clearly shown that in primary cultures of dog thyroid cells, insulin promotes protein accumulation, while TSH, in the presence of insulin, triggers DNA synthesis (7).…”
Section: Introductionmentioning
confidence: 99%
“…(8,13) and with an increase in the phosphorylation state of Rb (13), leading to the activation of cyclin⅐Cdk complexes and the progression of the cells through the cell cycle. TSH cell cycle induction is counteracted by cytostatic signals such as TGF-␤1 (13) and somatostatin (8,16,17). TGF-␤1 interference with TSH action has been studied in FRTL-5 cells (13); however, the mechanism of interference between somatostatin and TSH is unknown.…”
mentioning
confidence: 99%